Comparative Study and Simulation of Mid-range Wireless Power Transfer at Various Transmission Distance - Tan S.Y.; Yap J.X.; Lee H.J. (Institute of Physics Publishing, 2023)
Electric fields; Energy transfer; Green computing; Magnetic resonance; Magnetism; Comparative studies; CST microwave studio; Electronic device; Magnetic resonance couplings; Magnetic waves; Transmission distances; Wireless power transfer; Inductive power transmission